UCP2 promotes NSCLC proliferation and glycolysis via the mTOR/HIF‐1α signaling - Cailu Song; Qing Liu; Jing Qin; Lingrui Liu; Zhigang Zhou; Han Yang (Cancer Medicine, 2024)
Abstract Background Metabolic disturbance is a hallmark of cancers. Targeting key metabolic pathways and metabolism‐related molecular could be a potential therapeutic approach. Uncoupling protein 2 (UCP2) plays a pivotal part in the malignancy of cancer and its capacity to develop resistance to pharmaceutical interventions. However, it is unclear about the mechanism of how UCP2 acts in the tumor growth and metabolic reprogramming process in non‐small cell lung cancer (NSCLC). Methods Here, we conducted qRT‐PCR to investigate the expression of UCP2 in both NSCLC tissues and cell lines. Subsequent functional studies including colony formation assay, CCK‐8 assay, and glycolysis assay were conducted to investigate the functions of UCP2 in NSCLC. The regulatory mechanism of UCP2 toward the mammalian target of rapamycin (mTOR) and hypoxia‐inducible factor‐1 alpha (HIF‐1α) signaling in NSCLC was confirmed through western blotting. Results We observed a significant upregulation of UCP2 in both NSCLC tissues and cell lines. The increased expression of UCP2 has a strong association with a worse outlook. Silencing UCP2 remarkably dampened NSCLC cell proliferation and glycolysis capacities. Mechanically, UCP2 promoted NSCLC tumorigenesis partially via regulating the mTOR/HIF‐1α axis. Conclusion Taken together, we explored the functions as well as the mechanisms of the UCP2/mTOR/HIF‐1α axis in NSCLC progression, uncovering potential biological signatures and targets for NSCLC treatment.